2022
DOI: 10.1007/s11102-022-01266-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the diagnostic delay of acromegaly on bone health: data from a real life and long term follow-up experience

Abstract: Introduction Acromegaly is a chronic disease with systemic complications. Disease onset is insidious and consequently typically burdened by diagnostic delay. A longer diagnostic delay induces more frequently cardiovascular, respiratory, metabolic, neuropsychiatric and musculoskeletal comorbidities. No data are available on the effect of diagnostic delay on skeletal fragility. We aimed to evaluate the effect of diagnostic delay on the frequency of incident and prevalent of vertebral fractures (i-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
(80 reference statements)
1
9
0
Order By: Relevance
“…Our data confirm the presence of silent VFs in acromegalic patients. In our cohort, the prevalence of VFs, assessed by morphometric examination, was 11.4%, similar to that reported by Madeira and colleagues, but lower compared to other studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 23 , 41 , 61 ]. Different methods have been used to identify VFs in different studies, performing a radiographic examination of the spine rather than a morphometric examination in most cases.…”
Section: Discussionsupporting
confidence: 89%
“…Our data confirm the presence of silent VFs in acromegalic patients. In our cohort, the prevalence of VFs, assessed by morphometric examination, was 11.4%, similar to that reported by Madeira and colleagues, but lower compared to other studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 23 , 41 , 61 ]. Different methods have been used to identify VFs in different studies, performing a radiographic examination of the spine rather than a morphometric examination in most cases.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, biochemical control appears to be an important protective factor for skeletal damage. VFs may occur early in the natural disease history [ 25 ] and therefore normalization of biochemical activity should be mandatorily achieved as quickly as possible after the diagnosis, although this may not be enough to avoid fractures due to the known issue of diagnostic delay [ 24 , 82 ]. Additionally, concomitant diabetes mellitus, another common comorbidity of acromegaly [ 83 ], as well as a cause of bone fragility per se [ 84 ], was reported to increase the risk of fracture in active disease [ 85 ].…”
Section: Clinical Presentation Of Bone Involvement In Acromegalymentioning
confidence: 99%
“…Recently, we showed that prevalence of radiological thoracic VFs was associated with elevated presurgical random GH levels in patients recently diagnosed with acromegaly [ 25 ]. Moreover, another recent study suggested that a diagnostic delay >10 years may be a quite strong predictor of incident VFs [ 24 ].…”
Section: Clinical Presentation Of Bone Involvement In Acromegalymentioning
confidence: 99%
See 1 more Smart Citation
“…1 It is characterized by excessive growth hormone (GH) secretion by a pituitary neuroendocrine tumor (Pit-NET) causing bony and soft tissue enlargement and a series of life-threatening comorbidities such as cardiovascular, metabolic, and systemic diseases. 2,3 Oversecretion of the GH acting as a fertilizer for all the diseases and malignancies all over the body doubles the mortality rates in acromegaly patients compared with the general population. 4,5 Cardiovascular diseases, respiratory complications, and malignancies are theleading causes of death in 60, 25, and 15% of acromegaly patients, respectively.…”
Section: Introductionmentioning
confidence: 99%